Gradient Nanoporous Copper–Zinc Alloy Regulating Dendrite-Free Zinc Electrodeposition for High-Performance Aqueous Zinc-Ion Batteries - Liu, Jie; Jia, Jian-Hui; Chen, Li-Bo; Meng, Huan; Ran, Qing; Shi, Hang; Han, Gao-Feng; Wang, Tong-Hui; Wen, Zi; Lang, Xing-You; Jiang, Qing (Nano letters, 2025)
Zinc metal is an attractive anode material of aqueous batteries, but its practical use is persistently hampered by irregular zinc electrodeposition/dissolution and parasitic side reactions. Here we report engineering copper–zinc alloy with a composition- and structure-gradient nanoporous architecture as an effective strategy to regulate high-efficiency and dendrite-free zinc electrodeposition/dissolution for high-performance aqueous zinc-ion batteries. The dual-gradient nanoporous copper–zinc alloy electrodes not only guarantee electron and ion transport pathways but work as host materials with abundant zincophilic sites to guide zinc nucleation and deposition, enabling highly reversible zinc plating/stripping behaviors with low and stable voltage polarizations at various current densities and an ultralong lifespan of >6700 h. When assembled with carbon cloth-supported Zn x V2O5 cathode material, these outstanding electrochemical properties allow zinc-metal battery full cells to show exceptional rate capability and excellent stability. The capacity is retained at ∼95% after 5000 cycles at 5 A g–1, along with a Coulombic efficiency of ∼99.5%.